SERUM PROLACTIN LEVELS IN TYPE-II DIABETES MELLITUS WITH RETINOPATHY PATIENTS IN AND AROUND HYDERABAD - Abdullah Saad, Mohammed; Sabiullah, Mohammed; N, Vani (International Journal of Clinical and Biomedical Research, 2017)
Background & Objectives: Diabetes is a disease of metabolic dysregulation. Hyperglycemia and oxidative stress play a role in the development of late diabetic complications. Increased retinal vasopermeability occurs early in diabetes and is crucial for the development of sight-threatening diabetic retinopathy. Serum prolactin is proteolytically processed to vasoinhibins that inhibit the excessive retinal vasopermeability related to diabetic retinopathy. The aim is to study the role of serum prolactin and lipid profile in the pathogenesis of retinopathy in type 2 diabetics and to correlate the changes in serum prolactin levels. Methods: A case control study was done with 90 patients divided into 3 groups (healthy controls, Type 2 Diabetes without retinopathy and Type 2 Diabetes with retinopathy) with inclusion and exclusion criteria. Fasting blood samples were collected and fasting plasma glucose, serum Prolactin were measured. Multiple comparisons between different groups were done using ANOVA test. Results: In the present study decreased serum prolactin levels were observed in patients of Type 2 Diabetes with retinopathy compared to Type 2 Diabetes without retinopathy and controls. Mean ± S.D of Fasting plasma glucose, was highest in Group 3. Mean ± S.D of serum prolactin (7.737 ± 2.63) was low in Group 3. Interpretations & Conclusion: The circulating levels of prolactin were decreased in patients with diabetic retinopathy due to glycosylation and were higher in diabetic patients without retinopathy and healthy controls. Increased prolactin levels influence the progression of retinopathy after its intraocular conversion to vasoinhibins which can reduce the pathological retinal vasopermeability in diabetes and increase in prolactin can be considered to have protective role in pathogenesis of diabetic retinopathy and also may be considered as a treatment option for retinopathy. Key words: Prolactin; Diabetic retinopathy; Vasoinhibins; Retinal vasopermeability.